2018
DOI: 10.1108/maj-07-2017-1602
|View full text |Cite
|
Sign up to set email alerts
|

Related-party transactions: a review of the regulation, governance and auditing literature

Abstract: Purpose Several studies, especially in Asian economies, have investigated the antecedents, implications and consequences of related-party transactions (RPTs). This paper aims to review this literature to collate, gauge and critically discuss understandings of the relationship between RPTs and risk, with a particular focus on audit risk. Design/methodology/approach The paper discusses RPTs and how they have been associated with corporate scandals and the expropriation of shareholders’ wealth. RPTs are defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 89 publications
0
20
0
1
Order By: Relevance
“…Transfer pricing implementation can be evaluated using related party transactions of assets and liabilities (RPTAL) and transfer pricing intensity (TPI). Effective corporate governance has been proven to reduce the negative impact of related party transactions (El-Helaly, 2018). It means that the better the quality of the corporate governance mechanism by the proportion of board members of Commissioners', the more transfer pricing through RPTAL and TPI can be prevented.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Transfer pricing implementation can be evaluated using related party transactions of assets and liabilities (RPTAL) and transfer pricing intensity (TPI). Effective corporate governance has been proven to reduce the negative impact of related party transactions (El-Helaly, 2018). It means that the better the quality of the corporate governance mechanism by the proportion of board members of Commissioners', the more transfer pricing through RPTAL and TPI can be prevented.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…FCS can execute any contract with related parties (RPT) in an abusive way because of their concealed identity (Aswadi et al, 2011;Fooladi and MAJ 36,4 Farhadi, 2019). Additionally, the business landscape setting in Malaysia, with highly concentrated ownership (Claessens et al, 2000), weak governance and legal enforcement and insufficient protection of minority shareholders' rights, make it easy for FCS to manipulate their controlled companies to engage in RPTs (Gordon et al, 2004;Peng and Jiang, 2010;El-Helaly, 2018;Fooladi and Farhadi, 2019). In Malaysia, the controlling shareholder either uses pyramidal or cross-held ownerships to exert control over a chain of companies by hiding their substantial direct ownership to prevent an unfavorable response from investors.…”
Section: Theory Literature Review and Hypothesesmentioning
confidence: 99%
“…History has shown that opportunistic controlling shareholders, specifically FCS, use RPTs excessively as a tool for wealth expropriation (Ariff and Hashim, 2013;Bona-S anchez et al, 2017;Jian and Wong, 2010;Kang et al, 2014;Munir et al, 2013;Wong et al, 2015). This situation is more difficult in developing countries with weak corporate governance enforcements and insufficient legal protection mechanisms for shareholders (Peng and Jiang, 2010;El-Helaly, 2018), such as Malaysia (Aswadi et al, 2011;Munir et al, 2013). This study uses Malaysia, which is described as a networked economy (Gomez et al, 1999;Gul, 2006), as a natural setting to demonstrate the role of the network (ACR and FCS) in audit monitoring effectiveness (RPT disclosure).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on related party transactions identified the potential for negative use of such transactions, referring to that use as "tunneling." This case involves the use of related party transactions by controlling shareholders to expropriate funds from the firm to themselves at the expense of minority shareholders (Johnson et al, 2000;Utama and Utama, 2009;Chen et al, 2011;Williams and Taylor, 2013;Kang et al, 2014;Boateng and Huang, 2017;Habib et al, 2017a;Limanto and Herusetya, 2017;Abdul Rasheed and Mallikarjunappa, 2018;El-Helaly, 2018). Some methods of performing such transactions include transfer pricing, selling assets for profit, issuing securities to related parties for a low price and making excessive payments to executive managers, typically family members of the controlling owners (Utama and Utama, 2009).…”
Section: Related Party Transactions and Earnings Managementmentioning
confidence: 99%